Resilience, Stress and Subjective Well-Being among Medical Co-Assistants during COVID-19 Pandemic - Anggreini, Risa; Meldi, Nadia Amanda; Rachmawati, Arini; Nabila, Syaikha; Iskandarsyah, Aulia (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Medical co-assistants are at significant risk during the COVID-19 pandemic due to exposure to more substantial stressors, including handling patients, academic pressure, and reduced rest times. Moreover, their continuous exposure to disease during the COVID-19 pandemic places them in significant psychological distress. These challenges can potentially affect their subjective well-being. Effective stress management strategies are imperative to reduce susceptibility to adverse consequences. Resilience has been identified as a key protective factor against the detrimental impact of stress. A study involving 102 medical students who became co-assistants during the COVID-19 pandemic investigated the relationship between resilience, stress, and subjective well-being among medical co-assistants. The study found that resilience among medical co-assistants in Indonesia was negatively correlated with stress and negative affect, and positively correlated with life satisfaction, positive affect, and affective balance in subjective well-being. Resilience plays a crucial role in helping individuals recover from challenges and failures, viewing these setbacks as opportunities for growth and learning. This positive outlook contributes to increased positive affect and enhances their subjective well-being. Ultimately, this lowers their stress levels and reduces negative aspects that may impede their performance as medical co-assistants.